If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x-8)=2x+6
We move all terms to the left:
3(x-8)-(2x+6)=0
We multiply parentheses
3x-(2x+6)-24=0
We get rid of parentheses
3x-2x-6-24=0
We add all the numbers together, and all the variables
x-30=0
We move all terms containing x to the left, all other terms to the right
x=30
| 8t=30+3t | | q-971/(-3)=(-9) | | -6=-5u+2(u-6) | | 10=s3+1 | | k2=9k-18 | | a/6+6=-10 | | -10(j+487)=280 | | 45=7(z-3) | | (2p-7)2=22 | | z+15/(-6)=(-6) | | 2(4x+1)=3x+27 | | 3(r+1.6)−8r=9.53(r+1.6)-8r=9.5 | | -2(-7+6r)=14+r | | b/9-2=2 | | 5x+16=x-12 | | (3a-2)2=30 | | q+44/9=10 | | 0.44x+0.2x=87 | | 2x+x+8=180 | | 4x+2=2x-22 | | 2x+4-3x=-9+x+5 x=-3 x=4 x=-4 x=3 | | 2(2y-4=12 | | (k+6)2=32 | | 4m+4=-8 | | -4.5=0.5(x-7.1 | | 0.4x+0.2x=87 | | 16.43*x5=1 | | 3t-5t=36 | | 5x+1=3-4 | | 3x+2(4x-6)=10 | | -2+2n=-6 | | -4(x+7)=-9x+17 |